2007
DOI: 10.1007/s11191-007-9076-8
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the role of the personal narrative in teaching controversial socio-scientific issues

Abstract: Citizens participating in contemporary socio-scientific issues (SSI) need to draw on local knowledge and personal experience. If curricular developments in the teaching of controversial SSI are to reflect contemporary notions of citizenship then the personal narrative is an indispensable instrument in bridging the gap between the local/personal and the emergent science. In the context of controversy personal narratives help contending parties to see events in the light of those who do not share their views. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 54 publications
1
23
0
3
Order By: Relevance
“…These issues are related generally to people's daily life activities (Kolstø, 2001). These activities may include efficient energy usage (Acar, Turkmen & Roychoudhury, 2010), global warming (Cook, 2012, Reis & Galvão, 2009, nuclear/radioactive wastes (Morris, 2014;Lee, Abd-El-Khalick & Choi, 2006;Tal, Kali, Magid & Madhok, 2011) and stem cell (Levinson, 2008;Reis & Galvão, 2009;Sadler, Chambers & Zeidler, 2004;Shea, 2013) as well as gene therapy (Tal et al, 2011, Zohar & Nemet, 2002. For example; Acar et al (2010) suggest in their study on decision-making, nature of science, and argumentation that argumentation exercises should be definitely made.…”
Section: Introductiomentioning
confidence: 99%
“…These issues are related generally to people's daily life activities (Kolstø, 2001). These activities may include efficient energy usage (Acar, Turkmen & Roychoudhury, 2010), global warming (Cook, 2012, Reis & Galvão, 2009, nuclear/radioactive wastes (Morris, 2014;Lee, Abd-El-Khalick & Choi, 2006;Tal, Kali, Magid & Madhok, 2011) and stem cell (Levinson, 2008;Reis & Galvão, 2009;Sadler, Chambers & Zeidler, 2004;Shea, 2013) as well as gene therapy (Tal et al, 2011, Zohar & Nemet, 2002. For example; Acar et al (2010) suggest in their study on decision-making, nature of science, and argumentation that argumentation exercises should be definitely made.…”
Section: Introductiomentioning
confidence: 99%
“…Levinson (2008) reported that socioscientific issues drive much of the content in science courses around the world. He added that "prominent reasons given for the inclusion of such [socio-scientific] issues tend to link them to scientific literacy, to focus on the need for scientific knowledge, to help in decision-making and to sustain democracy" (p. 856).…”
Section: Socioscientific Issuesmentioning
confidence: 99%
“…Schooling is supposed to challenge local traditions (Hlebowitsh, 2005), and unearthing controversies can help shift student focus from authoritative narratives and perspectives to heterogeneous micronarratives that draw on and challenge local and individual knowledge (Levinson, 2008). Addressing controversial issues can help widen and enlarge student experiences in terms of the normativity of topics, but also in the multiple perspectives entertained among teachers and peers to establish understandings and formulate solutions without succumbing to the tyranny of forced meaning (Giroux, 1983) and the often seductive appeal of prevailing belief and opinion.…”
Section: The Importance Of Controversial Issues For Democracymentioning
confidence: 99%